Crystalline silica heterojunction solar cell structure - WANG LEI; XU XIN; ZHANG WENBIN; HUANG HAIBIN; WANG YUEBIN; LI XINGBING; PENG DEXIANG (2018)
The utility model relates to a crystalline silica heterojunction solar cell structure is on the one side of the n of making herbs into wool type crystal silicon chip or the two sides silica -based film of deposit intrinsic amorphous, amorphous -silicon -doped thin film, indium oxide titanium ITiO film in proper order. The utility model discloses a crystalline silica heterojunction solar cell structure homogeneity, stable good, deposition rate can satisfy the needs of high speed production soon, a crystalline silica heterojunction solar cell, the yields can be greater than 99.5% that is used for crystalline silica heterojunction solar cell's large -scale production, and can obtain conversion efficiency and be greater than 22.5% . 本实用新型涉及种晶体硅异质结太阳电池结构，在制绒的n型晶体硅片的面或两面依次沉积本征非晶硅基薄膜、掺杂非晶硅薄膜、氧化铟钛ITiO薄膜。本实用新型的晶体硅异质结太阳电池结构均匀性、稳定性好，沉积速率快可满足高速率生产的需要；用于晶体硅异质结太阳电池的大规模生产，可得到转换效率大于22.5％的晶体硅异质结太阳电池，良品率可大于99.5％。